2017
DOI: 10.1039/c6lc01495j
|View full text |Cite
|
Sign up to set email alerts
|

Pipetting-driven microfluidic immunohistochemistry to facilitate enhanced immunoreaction and effective use of antibodies

Abstract: Immunohistochemistry (IHC), which has been used to detect antigens in cells of a tissue section using an immunoreaction between an antibody and an antigen, is a practical tool for identifying the type and stage of diseases in cancer diagnosis and scientific research. However, conventional IHC requires long, laborious process times and high costs. Although microfluidic IHC platforms have been developed to overcome these limitations, the application of microfluidic IHC in real-world environments is still limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…This phenomenon can be implemented by various strategies, for example, simply by flipping the probe incubation chamber continuously or by tilting the container of probe solution back and forth . It can also be achieved by lateral flow of probe solution in microfluidic device generated by the negative pressure of pipetting . Multiple studies demonstrated that CDR shortened assay time from hours to minutes in common surface bioassays like ELISA and immunofluorescence microscopy .…”
mentioning
confidence: 99%
“…This phenomenon can be implemented by various strategies, for example, simply by flipping the probe incubation chamber continuously or by tilting the container of probe solution back and forth . It can also be achieved by lateral flow of probe solution in microfluidic device generated by the negative pressure of pipetting . Multiple studies demonstrated that CDR shortened assay time from hours to minutes in common surface bioassays like ELISA and immunofluorescence microscopy .…”
mentioning
confidence: 99%
“…As explained previously, micropumping and micromixing both enable precise, controlled, and rapid reactions, assays, and diagnostics tests. 8,37,63,64 While each of these functions is critical for many microfluidic applications, they remain discrete innovations. Having developed the sharp-edge based technology necessary to achieve both functions separately, herein we also demonstrated that by combining the design of sharp-edge structures for micropumping and micromixing together, concurrent pumping and mixing can be achieved on a single acoustofluidic chip.…”
Section: Resultsmentioning
confidence: 99%
“…For the IHC assay, we used a pressure-based reversible sealing method to seal the microfluidic channel by applying pressure on the chip that is in contact with the section slide. 19,24 However, the UV-curable PUA used in this work also has a rigid property after curing and causes a sealing problem. Since a typical microfluidic chip has a flat surface, it has a large contact area with the sample, thereby lowering the pressure applied to the channel surface.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 These advantages have led to the development of various microfluidic IHC platforms that are capable of performing complex assays, such as multiplexed biomarker screening on breast cancer tissue, 15,16 precise spatial control of immunostaining, 17,18 and enhanced immunoreaction in a reduced process time. 19 An accurate IHC analysis for biomarker quantification was also demonstrated using a quantum-dot based microfluidic double-staining method, 20,21 a microfluidic tissue processor for formalin-fixed sections, 22 and frozen sections, 23 and standardization of immunostaining quality. 24 Although these microfluidic techniques have contributed to expand the potential of the IHC process, there are still a limited number of applications.…”
Section: Introductionmentioning
confidence: 99%